Transforming growth factor-alpha-induced DNA synthesis and c-myc expression in primary rat hepatocyte cultures is modulated by indomethacin. - Skouteris, G; Mcmenamin, M (1992)
Primary hepatocytes stimulated with epidermal growth factor (EGF) secrete prostaglandins into the culture medium as soon as 1 h after the addition of the EGF. Transforming growth factor-alpha (TGF alpha), a potent hepatocyte mitogen, shares the same receptor with EGF, and its expression is increased after partial hepatectomy. TGF alpha is also secreted in culture. We have observed that TGF alpha induced hepatocyte DNA synthesis (30 h after addition) and at the same time stimulated the production of prostaglandins E2 and F2 alpha by the cultured hepatocytes. Indomethacin at 20-100 microM inhibited the TGF alpha-induced hepatocyte DNA synthesis, and this effect was specifically due to the inhibition of prostaglandin formation. Indomethacin also inhibited a TGF-alpha-induced increase in hepatocyte c-myc expression, indicating that prostaglandins mediate this increase, as previously shown for EGF. TGF alpha increased the expression of the EGF receptor gene, and this was prevented by the presence of an antibody against TGF alpha in the culture medium. We therefore suggest that TGF alpha induces hepatocyte proliferation either through coupling with its receptor (i.e. the EGF receptor) or by subsequent phosphorylation of lipocortin I. This leads to activation of phospholipase. A2, which seems to regulate the metabolism of arachidonic acid and the formation of prostaglandins. Thus hepatocyte proliferation in vitro appears to be controlled by a self-regulatory autocrine pathway involving activation of phospholipase A2 and secretion of prostaglandins and TGF alpha.